PENGARUH SOFT SKILL, EFIKASI DIRI DAN KEAKTIFAN BERORGANISASI TERHADAP KESIAPAN KERJA PADA MAHASISWA (STUDI KASUS DI UNIVERSITAS 17 AGUSTUS 1945 SURABAYA PROGRAM STUDI MANAJEMEN ANGKATAN 2021) - Jessica Yuli Hana; Sumiati Sumiati (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to examine the impact of soft skills, self-efficacy, and organizational participation on thew ork readiness of management study program students, class of 2021 at Universitas 17 Agustus 1945 Surabaya, using a quantitative approach with a questionnaire as an instrument to collect data. The sample taken was 75 respondents, consisting of active students of the management study program class of 2021 at Universitas 17 Agustus 1945 Surabaya. The data were analyzed using IBM SPSS version 25 with the multiple linear regression analysis method. The findings of the study showed that all variables tested were proven valid and reliable. The results of the multiple linear regression analysis revealed that soft skills, self-efficacy, and activeness in organizations had a positive and significant effect on students' work readiness. The T test indicated that each independent variable made a significant contribution, while the F test showed that the three variables simultaneously had a significant effect on work readiness. The coefficient of determination (R²) showed that 84% could be explained by the factors studied, while the remaining 16% was influenced by other factors. The findings of this study provide important recommendations for students to improve their work readiness to be better prepared to face the challenges of the world of work in the future. Keywords: Soft skill; Self-efficacy; Organizational Activity; Future Work Readiness